2021
DOI: 10.1007/s10453-021-09708-5
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of environmental microorganisms associated with COVID-19 affected patients

Abstract: To clarify the characteristics and distribution of hospital environmental microbiome associated with confirmed COVID-19 patients. Environmental samples with varying degrees of contamination which were associated with confirmed COVID-19 patients were collected, including 13 aerosol samples collected near eight patients in different wards, five swabs from one patient’s skin and his personal belongings, and two swabs from the surface of positive pressure respiratory protective hood and the face shield from a phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…None of the air samples collected in the ICU ward of this study was found positive to SARS-CoV-2, according to the Allplex 2019-nCoV Assay which has an analytical sensitivity of 50 copies per reaction (3 viral copies per microliter of sample). Our results are consistent with those from previous studies, which detected SARS-CoV-2 at very low rates, likely for weak ability of the virus to be transmitted by aerosol particles (Ghaffari et al, 2021 ; Hemati et al, 2021 ; Liu et al, 2020 ; López et al, 2021 ; Zhang et al, 2021 ). The first study on the SARS-CoV-2 detection in air samples was performed by Liu et al ( 2020 ) using a droplet digital Polymerase Chain Reaction (ddPCR) method, which was carried out according to the manufacturer’s instructions for the QX200 Droplet Digital PCR System (Bio-Rad).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…None of the air samples collected in the ICU ward of this study was found positive to SARS-CoV-2, according to the Allplex 2019-nCoV Assay which has an analytical sensitivity of 50 copies per reaction (3 viral copies per microliter of sample). Our results are consistent with those from previous studies, which detected SARS-CoV-2 at very low rates, likely for weak ability of the virus to be transmitted by aerosol particles (Ghaffari et al, 2021 ; Hemati et al, 2021 ; Liu et al, 2020 ; López et al, 2021 ; Zhang et al, 2021 ). The first study on the SARS-CoV-2 detection in air samples was performed by Liu et al ( 2020 ) using a droplet digital Polymerase Chain Reaction (ddPCR) method, which was carried out according to the manufacturer’s instructions for the QX200 Droplet Digital PCR System (Bio-Rad).…”
Section: Resultssupporting
confidence: 93%
“…Both samples were taken from the places which had higher concentrations of PM. Zhang et al ( 2021 ) collected 12 bioaerosol samples and 7 swab samples from the environments hosting COVID-19 patients in ICU hospital wards. DNA was extracted and purified from 200 μl aerosol samples or swabs according to the instruction of DNA Mini kit DP316 (Tiangen).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Table 2 displays positive and significant ρ values among Corynebacterium and Staphylococcus (0.92), Acinetobacter and Pseudomonas (0.77), Bacteroides and Prevotella (0.78), Bacteroides and Streptococcus (0.76), and Prevotella and Streptococcus (0.83). The comparison of these results with the hierarchical clustering of clades on the left-side of Figure 1 c shows that the detected significant proportionalities between the abovementioned pairs of pathogenic genera correspond to double clades in the dendrogram of Figure 1 c. Moreover, these pathogens may all cause hospital-associated infections, as discussed in the previous section (e.g., [ 58 , 61 , 69 , 76 , 77 , 78 , 79 ]). The high proportionalities found among Bacteroides , Prevotella, and Streptococcus can also be due to the fact that they are commonly found in the upper respiratory tract (e.g., [ 80 , 81 ]).…”
Section: Resultsmentioning
confidence: 54%
“…Corynebacterium , Sphingomonas , and Staphylococcus are the only three genera detected in all the samples with high and positive CLR values, as reported in Table S1 . In fact, they are among the prevailing genera within hospital wards (e.g., [ 60 , 61 ]). Corynebacterium is a skin colonizer that also has been isolated in patients after prolonged hospitalization (e.g., [ 61 , 62 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation